A study of human choline kinase a (hCK-a) in patients with ischemic heart disease (ihd) and heal thy volunteers - Chia, Phee Phee (Universiti Sains Malaysia, 2008)
Ischemic heart disease (IHD) is predicted to become the dominant cause of mortality worldwide by 2030. As a silent yet eventually fatal disease, prevention and early detection through discovery of cardiac biomarker are the best resolution for IHD. Human choline kinase a (hCK-a) was investigated for its possibility as a cardiac biomarker in this study. The aim of this study is to investigate the differences in the protein level and mRNA expression of hCK-a between IHD patients and healthy controls. Blood samples from 10 IHD patients and 10 healthy volunteers were analyzed for mRNA expression using RT-PCR. Western blot was performed as a checkpoint for detection of hCK-a protein in blood. Subsequently, ELISA test was conducted to measure the protein concentration of hCK-a protein. C-reactive protein (CRP) was used as a standard reference in this study to provide a parameter to distinguish between both study groups. Statistical analysis was performed to investigate the relationship between hCK-a with IHD. Parametric test was performed using independent t-test meanwhile non-parametric test was performed using Mann-Whitney test. As anticipated, CRP was found to be significant higher in expression both in mRNA level and protein level (Independent t-test, p<0.001; Mann-Whitney test, p= 0.019). In this study, a significant lower level of hCK-a2 mRNA expression in IHD patients was revealed (Independent ttest, p=0.032). However, total hCK-a mRNA expression was found to have no significant different between IHD patients and healthy volunteers (Mann-Whitney test, p=0.705). Protein expression level of hCK-a was found to be significantly lower in lHD patients as compared to healthy volunteers (Mann-Whitney test, p=0.014). Albeit preliminary, this study found that there may be a profound relationship between hCK-a and IHD.